Mainstreaming Restorative Justice in Termination of Prosecution in Indonesia - Femmy Silaswaty Faried; Hadi Mahmud; Suparwi Suparwi (Lembaga Contrarius Indonesia, 2022)
By law, under the principle of opportunity, public prosecutors have been entitled to the authority to proceed or terminate the criminal cases under their authority. However, the termination of prosecution by the attorney generals is mostly not followed by a victim-oriented settlement. In this case, the principle of opportunity is not in line with the victim interest. On the other hand, the direction of legal reform in Indonesia promotes restorative justice approach in every criminal case settlement. In this regard, this article aims to investigate the way to implement restorative justice in case terminations by General Attorney of Indonesia. This research relies on socio-legal approach. Data were collected through the investigation of regulations and works of literature related to the termination of prosecution of criminal cases and restorative justice. The result of this study indicates that the regulation concerning termination of prosecution based on restorative justice is obviously departed from the public needs. According to General Attorney Regulation, restorative justice which is oriented to the public interest has the chance to be implemented as the basis for termination of prosecution of criminal cases; therefore, the penal court can be addressed as the last option (ultimum remidium).